Fontes e doses de fósforo em alho vernalizado livre de vírus - Jacon, Camila Paula Rossetto Pescatori [UNESP] (2016)
The use of virus-free garlic plants, associated with other technologies can increased productivity in vernalized garlic growing. However, these plants have different productive behavior from the infected plants, requiring the adequacy of management techniques used for the culture until then. Studies on virus-free garlic plants nutrition of are not conclusive. In order to achieve high productivity and considering the characteristics of tropical soil, phosphate fertilizers have been used in high doses. So, this study aimed to vertify the effect of phosphate fertilization on vernalized virus-free garlic growing. Therefore three experiments were carried out in subsequent years in growing field, in the Santa Juliana - MG. In the first experiment were evaluated two sources (SS and SS + T) and 5 doses of phosphorus (0, 100, 200, 300, 400 mg dm-3) in 4 replications. It was observed that the results were little influenced by the P sources and that higher doses of P applied occasioned reduction in yield and quality of the bulbs. In experiment 2 were evaluated five doses of P (0, 70, 140, 210, 180 and 350 mg dm-3) in 4 replicates using SS+T. It was found that, as in the first experiment, at the higher doses of P, there was a decrease of production. Due to a rain occurred in the differentiation stage, there was incidence of secondary bulb growth and it was verified that plants with this anomaly increased with P doses rising. The third experiment was carried out evaluating five levels of P (0, 50, 100, 150, 200 and 250 mg dm-3) in 4 replicates and it was also verified that there was a decrease in production at the highest dose. The use of 200 mg dm-3 of P, with the source superphosphate + thermophosphate, in soil with high phosphorus initial level, provided higher yield and percentage of bulbs in more valued classes.